Heart-In Education Financing Model In Improving The Quality Of Education At The Almuslim Peusangan Foundation Bireuen District - Mangkuwinata, Sonny Muhammad Ikhsan; Yuniarsih, Tjutju; Kurniady, Dedy Achmad; Nurdin, Diding (LPPM Universitas PGRI Sumatera Barat, 2024)
This study aims to develop a Heart-In Education Financing Model to Improve the Quality of Education at the Almuslim Peusangan Foundation, Bireuen Regency. This research design carries a qualitative approach and Design Based Research (DBR) method to explore the dynamics of education financing and its impact on the quality of education at the Almuslim Peusangan Foundation. The qualitative approach was chosen to explore in-depth understanding, capture nuances, and gain contextual insights in the implementation of the financing model. Overall, the description of education financing at the Almuslim Peusangan Foundation reflects the location of the research was carried out at the Almuslim Peusangan Foundation, Peusangan District, Bireuen Regency. The subjects of the study were key informants of the Almuslim Peusangan Foundation in Bireuen Regency, which has an important role in the policy and implementation of education financing. During the visit, researchers conducted interviews and collected information at Almuslim University, Almuslim Islamic Institute and Almuslim Integrated Islamic Boarding School. The ongoing efforts to manage funds efficiently and effectively, although there are still several challenges that need to be overcome. With a more planned approach and more effective strategies, the foundation can improve the quality and access to education and achieve better financial sustainability. Efforts to continue to improve efficiency, transparency, and accountability in the use of funds, as well as establishing cooperation with external parties, are important steps in achieving better education goals in the future. These findings indicate that with good management and the right strategies, the foundation can overcome various challenges and continue to make significant contributions to improving the quality of education and community welfare